2017
DOI: 10.1074/jbc.m117.784249
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum–mitochondria junction is required for iron homeostasis

Abstract: The endoplasmic reticulum (ER)-mitochondria encounter structure (ERMES) is a protein complex that physically tethers the two organelles to each other and creates the physical basis for communication between them. ERMES functions in lipid exchange between the ER and mitochondria, protein import into mitochondria, and maintenance of mitochondrial morphology and genome. Here, we report that ERMES is also required for iron homeostasis. Loss of ERMES components activates an Aft1-dependent iron deficiency response e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 48 publications
2
29
1
1
Order By: Relevance
“…68,73 Also, dominant mutations in VPS13 suppress known ERMES complex-deficient phenotypes, probably by increasing the formation or function of vCLAMPs. 73,75 This role in MCS is in agreement with the current reports that purified Vps13 exhibits ATP-stimulated binding to yeast membranes 54 and interacts with various membrane lipids, as described above. Moreover, association of Vps13 with lipids is important for its localization, as microscopy studies showed that Vps13-GFP is abnormally accumulated in large perivacuolar membrane compartments of endocytic origin 57 and I2749R (see Table 2 for a list of human missense mutations investigated in yeast).…”
Section: Yeast As a Model To Study Vps13 Proteinssupporting
confidence: 92%
See 1 more Smart Citation
“…68,73 Also, dominant mutations in VPS13 suppress known ERMES complex-deficient phenotypes, probably by increasing the formation or function of vCLAMPs. 73,75 This role in MCS is in agreement with the current reports that purified Vps13 exhibits ATP-stimulated binding to yeast membranes 54 and interacts with various membrane lipids, as described above. Moreover, association of Vps13 with lipids is important for its localization, as microscopy studies showed that Vps13-GFP is abnormally accumulated in large perivacuolar membrane compartments of endocytic origin 57 and I2749R (see Table 2 for a list of human missense mutations investigated in yeast).…”
Section: Yeast As a Model To Study Vps13 Proteinssupporting
confidence: 92%
“…Deletion of VPS13 is synthetically lethal in combination with mutations of MMM1 , encoding an integral ER membrane protein that is a subunit of the ER mitochondria encounter structure (ERMES) complex, tethering the ER and mitochondria . Also, dominant mutations in VPS13 suppress known ERMES complex‐deficient phenotypes, probably by increasing the formation or function of vCLAMPs . This role in MCS is in agreement with the current reports that purified Vps13 exhibits ATP‐stimulated binding to yeast membranes and interacts with various membrane lipids, as described above.…”
Section: Yeast As a Model To Study Vps13 Proteinssupporting
confidence: 89%
“…This includes higher levels of iron from increased expression of iron transporters and lower endogenous zinc levels. These petite yeast were induced by loss of the mitochondrial genome and petite yeast caused by other types of mutations also had differences in internal metals and regulation in the iron regulome (39). There is an interplay between metal levels, as zinc transporters are also important for responding to high levels of copper (24).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative, but far less studied potential mechanism for heme distribution is through mitochondrial membrane contact sites (Hanna et al, 2017; Piel et al, 2019; Reddi and Hamza, 2016). Endoplasmic reticulum (ER)-mitochondrial encounter structures (ERMES), one type of mitochondrial-ER contact site (Elbaz-Alon et al, 2014), are highly dynamic tethers that physically link the mitochondrial and ER networks and have been proposed to play a role in the transfer of lipids and regulate iron homeostasis (Lackner, 2019; Murley and Nunnari, 2016a; Xue et al, 2017). The frequency of ERMES is in part dependent on mitochondrial division (Elbaz-Alon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%